The Calculation Analysis of Total Productive Maintenance (TPM) on the Plumatex FFS894 Machine Using the Overall Equipment Effectiveness (OEE) Method at PT.XYZ Pharmaceutical Company - et. al., Muhamad Anwar Septiana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
PT.XYZ is a company engaged in the pharmaceutical sector which is inseparable from problems related to the effectiveness of machines or equipment causes by the effect of Six Big Losses. Therefore, we need effective and efficient steps in the maintenance of machines or equipment to overcome and prevent these problems. Total Productive Maintenance (TPM) is a management principle to increase the productivity and efficiency of the Company's production by using machines effectively. Incorrect handling and maintenance of machines will result in losses which are called Six Big Losses. The first step in the effort to increase production efficiency at PT. XYZ Company is to measure the effectiveness of the Plumatex FFS894 machine using the Overall Equipment Effectiveness (OEE) method which then measures Six Big Losses to find out the amount of efficiency lost in the Six Big Losses factor. With a cause and effect diagram can analyze the actual problem which is the main cause of the high losses resulting in the low effectiveness of the Plumatex FFS894 machine. The conclusion on the Plumatex FFS894 machine is that the OEE value for the period of August 2020 to January 2021 range from 77.76% to 86.82%, with an average OEE value of 82.73%. So, the Plumatex FFS894 machine has not reached the ideal conditions (≥85%). The factor that made the biggest contribution which result in the low effectiveness of using the Plumatex FFS894 machine which is the main priority for improvement is Reduced Speed ​​Losses with a percentage of 25.76% and Idling and Minor Stoppage Losses with a percentage of 21.09%.